Evaluating the Psychometric Properties of the Mental Health Continuum Short-Form - Andi Tenri Faradiba; Anindya Dewi Paramita; Airin Triwahyuni; Urip Purwono (Bulletin of Counseling and Psychotherapy, 2023)
The Mental Health Continuum-Short Form (MHC-SF) is a tool designed to evaluate an individual's overall mental health and well-being, encompassing emotional, psychological, and social dimensions. Adopted in several countries, including Portugal, South Korea, Italy, and France, the present study aims to adapt the MHC-SF for the Indonesian context and assess its psychometric properties. The adaptation followed the ITC Guidelines for Adapting Tests, an international standard for adapting and psychometrically testing measuring instruments. The content validity was evaluated through the involvement of three experts and four reviewers in assessing the results of the Indonesian translation. Data was collected from a sample of 256 students, who participated by filling out an online questionnaire. The results of the content validity indicated that the 14-item instrument was relevant to the purpose of measuring well-being. Construct validity showed a three-factor structure (emotional well-being, psychological well-being, and social well-being) with a fit model, and all items had a factor loading value greater than .5, indicating their validity. The reliability test revealed consistent results with alpha coefficient values in the range of .7 to .8 for the three dimensions, demonstrating that the instrument can provide consistent results when used on the same individual in different situations. This study concludes that the Indonesian version of the MHC-SF is valid and reliable for assessing an individual's well-being.